Time and eternity in Jewish mysticism : that which is before and that which is after - Ogren, Brian. (Studies in Jewish History and Culture, 2015)
Time and eternity are concepts that have occupied an important place within Jewish mystical thought. This present volume gives pride of place to these concepts, and is one of the first works to bring together diverse voices on the subject. It offers a multivalent picture of the topic of time and eternity, not only by including contributions from an array of academics who are leaders in their fields, but by proposing six diverse approaches to time and eternity in Jewish mysticism: the theoretical approach to temporality, philosophical definitions, the idea of time and pre-existence, the idea of historical time, the idea of experiential time, and finally, the idea of eternity beyond time. This multivocal treatment of Jewish mysticism and time as based on variant academic approaches is novel, and it should lay the groundwork for further discussion and exploration.